STRATEGI PENGEMBANGAN DAYA TARIK WISATA PEMANDIAN SERAYU LESTARI DI SAMARINDA - Yunita Marsari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
Serayu Lestari Baths is an artificial tourist destination and one of the leading tourist destinations in Samarinda. This study aims to find out and analyze how the strategy for developing the tourist attraction of the Serayu Lestari Baths in Samarinda and what obstacles are faced by managers in developing Serayu Lestari Baths tourism. This type of research is qualitative. Sources of research data are Key Informants and Informants. Data collection techniques in this study were in the form of observation, interviews, documentation and literature study. Data analysis techniques used are data redaction, data presentation and conclusion drawing. The results of this study indicate that the Serayu Lestari Baths Tourism Attraction Development Strategy in Samarinda, the manager of the Serayu Lestari Baths has made developments in terms of, Accessibility has made road improvements, made directions to tourist sites and can be passed by public or online transportation. In Amenities, the manager has completed adequate facilities for visitors. In Hospitality at the Serayu Lestari Baths, the surrounding community and employees are very friendly to visitors. In the Serayu Lestari Baths Attraction, several attractions are still under construction. And the obstacle in developing the sustainable Serayu Baths is the lack of budget funds to develop the attractions in the Serayu Lestari Baths.